Pola Pendayagunaan Zakat Pada Lembaga Amil Zakat, Infak Sedekah Muhammadiyah (LAZISMU) Sumatera Barat - thaheransyah thaheransyah; Syamsurizal Syamsurizal; Zahirman Zahirman (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The existence of zakat institutions is one form of implementation of Islamic teachings. Specifically, the management of zakat becomes the main pillar in the Islamic pillars related to the obligation to pay zakat. West Sumatra LAZISMU is an Islamic philanthropic institution dedicated to empowering people and humanity through the utilization of zakat, infaq, shadaqah, waqf and other philanthropic funds from individuals, institutions, companies and other agencies. LAZISMU is a response to the fact that the Indonesian people are still largely in a state of poverty, social structures are increasingly fragile, social disparities are increasingly large and geographically located in disaster prone areas. In the meantime, West Sumatra, whose population is predominantly Muslim and still holds strong religious principles, has the potential for zakat, infaq, shadaqah, waqf and others which are quite high. However, this great potential has not been managed and utilized optimally so that it has not yet had a significant impact on the resolution of poverty and solving existing problems. The research method used is field research (field research) researchers using the Phenomenological approach, data collected through observation, documents and interviews, then will be analyzed sequentially and interactionally consisting of three stages, namely: 1) Data reduction, 2) Data presentation, 3) Conclusions withdrawal or verification. The results revealed that the pattern of zakat utilization by LAZISMU West Sumatra is focused on productive utilization which consists of: 1. Microeconomic Empowerment 2. Empowerment of agriculture and animal husbandry (Agriculture and Livestock Empowerment) 3. Educational Development (Education Development) 4 Social Service and Da'wah (Social and Da'wah Services). It can be concluded that LAZISMU West Sumatra has tried well and planned in an effort to utilize zakat so that it is able to overcome the problems experienced by mustahik.